Diagnostic accuracy of angiography-based vessel fractional flow reserve after chronic coronary total occlusion recanalization. (3rd October 2022) - Scoccia, A; Scarparo, P; Neleman, T; Wilschut, J; Den Dekker, W; Zijlstra, F; Van Mieghem, N; Daemen, J; Diletti, R
Abstract: Background: Angiography-Based Vessel FFR (vFFR) demonstrated a strong correlation with invasive fractional flow reserve (FFR) in both a pre- and post-percutaneous coronary intervention (PCI) setting. However, the role of vFFR and its correlation with post-PCI FFR in chronic coronary occlusion (CTO) has not been evaluated yet. We sought to investigate the diagnostic performance of post-PCI vFFR with post-PCI FFR as a reference in patients undergoing successful CTO PCI. Methods: Between March 2016 and September 2019, a total of 80 patients from the FFR-SEARCH and FFR REACT studies underwent successful CTO recanalization [1, 2]). A total of 50 patients (median age 66 (IQR: 56–74) years, 76% were male) were eligible for the analysis. Median FFR was 0.89 (IQR: 0.84–0.94) while median vFFR was 0.91 (IQR: 0.85–0.94). Suboptimal physiological results, defined as FFR and vFFR <0.90, were identified in 26 (52%) and in 21 (42%) patients, respectively. A strong correlation (r=0.79) was found between vFFR and FFR with a mean bias of 0.013±0.051. Receiver-operating characteristics curve analysis revealed an excellent accuracy of vFFR in predicting FFR <0.90 (AUC: 0.97; 95% CI: 0.93–1.00). Conclusion: vFFR shows a good agreement with FFR and a high diagnostic accuracy for FFR ≤0.90 in patients undergoing successful PCI of a CTO lesion. Funding Acknowledgement: Type of funding sources: None.